Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.ppat.1006419
|View full text |Cite
|
Sign up to set email alerts
|

Competition between influenza A virus subtypes through heterosubtypic immunity modulates re-infection and antibody dynamics in the mallard duck

Abstract: Our overall hypothesis is that host population immunity directed at multiple antigens will influence the prevalence, diversity and evolution of influenza A virus (IAV) in avian populations where the vast subtype diversity is maintained. To investigate how initial infection influences the outcome of later infections with homologous or heterologous IAV subtypes and how viruses interact through host immune responses, we carried out experimental infections in mallard ducks (Anas platyrhynchos). Mallards were pre-c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 68 publications
(96 reference statements)
3
49
0
Order By: Relevance
“…This is a simplification of the course of an individual's infection with LPAIV. Yet, individual variation in time to clearing infections is substantial (e.g., Latorre-Margalef et al, 2009;Tolf et al, 2013), and dependent on previous exposure to the same or other strains or subtypes of LPAIV (e.g., Costa et al, 2010;Verhagen et al, 2015;Latorre-Margalef et al, 2017). We thus think that using a simplified process was justified, and does not overestimate time to recovery.…”
Section: Discussionmentioning
confidence: 98%
“…This is a simplification of the course of an individual's infection with LPAIV. Yet, individual variation in time to clearing infections is substantial (e.g., Latorre-Margalef et al, 2009;Tolf et al, 2013), and dependent on previous exposure to the same or other strains or subtypes of LPAIV (e.g., Costa et al, 2010;Verhagen et al, 2015;Latorre-Margalef et al, 2017). We thus think that using a simplified process was justified, and does not overestimate time to recovery.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to sequential inoculation with H3N8, inoculation of H3N8-infected animals with H4N5 led to a dramatic change in antibody repertoire, including a strongly boosted response to H3 and a broadening of the reactivity to other group 2 HAs, with a proportion of the response being driven by antibodies to the conserved stalk of HA. Interestingly, it has been shown that the degree of protection of mallard ducks after a secondary infection with a different virus subtype correlates to the similarity between HAs 5 and may be the result of reactivity of anti-stalk antibodies. The induction of broadly reactive anti-stalk antibodies has been reported in mice and humans that were sequentially exposed to different HA subtypes of the same group 30 , 32 , 33 , 36 , 37 , 38 , 39 (for example, H1 and H5), but this phenomenon has not been reported so far in avian species.…”
Section: Discussionmentioning
confidence: 99%
“…Mallard ( Anas platyrhynchos ) sera used in the study were available from a previously published study. 5 All work was approved by the University of Georgia Animal Care and Use Committee under AUP number A2013 05–021. Mallards were raised in captivity at the Animal Resources College of Veterinary medicine at the University of Georgia, and confirmed to be naive to influenza virus by nucleoprotein ELISA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our effort to construct relatively simple models allowing for comprehensive testing of a set of hypothesised drivers for local AIV infection dynamics, we had to make a considerable number of assumptions. Possibly the most important one is that we ignored the existence of viral subtypes, and that AIV infection might elicit subtype specific immunity against further infections (Latorre‐Margalef et al., ). However, ducks may show limited immune responses to AIV infection contrasting findings from, for example, chickens (Kida et al., ) and can quickly be reinfected with the same AIV subtype (Chaise et al., ) providing support for our simplifying approach to ignore potential antigenic variation in AIV infected mallards.…”
Section: Discussionmentioning
confidence: 99%